Prototipe Sistem Monitoring Rumah Walet Berbasis IoT - Muhamad Ariandi; Jerry Alvinser (Universitas Budi Darma, 2023)
Swallow's nest is one of the areas of business carried out by residents of the Tulung Selapan area, where many residents of the area make their houses part of the swallow's house, so that the houses where people live and the swallow's house merge. Problems often occur in swiftlet houses which cause unstable temperatures, poor air quality, and the sound of swallow call speakers that often turn off without a known cause. Where to carry out maintenance of the swallow house cannot be done at any time, only certain times that can be done by the swallow entrepreneur in checking the swallow house, namely when the swallow comes out. From these problems, the researcher aims to make a prototype of a swallow house monitoring tool which has several components such as temperature so that the condition of the swallow house is maintained at a temperature of 260C - 290C using a DHT22 sensor and a mistmaker. The heater automatically turns on at temperatures below 260C to keep the swiftlet house hot and if the temperature is above 290C a mistmaker is used as a cooler which will automatically turn ON. To maintain air quality using the MQ-2 sensor, and monitoring the current flowing to the swiftlet calling speaker using a DC voltage sensor with the help of Esp32 as a microcontroller. So with the existence of this swiftlet house prototype tool, swallows will feel comfortable and produce good quality swallow nests for entrepreneurs to make it easier to monitor swallows in their swallow houses. From the results of measurements and percentage calculations performed on each component of the tool sensor, nothing exceeds the tolerance value of 5% and the components used in this tool can work properly according to their functions. This monitoring system prototype tool can help swallow house entrepreneurs more easily control the condition of swallow houses and produce good quality swallow nests than before, so they have quite expensive selling prices.